Introducing gaseous transport fuel to Ireland: A strategic infrastructure framework. (June 2019) - Goulding, D.; Fitzpatrick, D.; O'Connor, R.; Browne, J.D.; Power, N.M.
Abstract: European Union legislation in the form of the Renewable Energy Directive 2009/28/EC and the Deployment of Alternative Fuels Infrastructure Directive 2014/94/EC have placed mandatory requirements on Member States to deliver sustainable forms of alternative transport infrastructure in order to reduce greenhouse gas emissions in the transport sector. However, there is currently little or no refuelling infrastructure to support the development of an alternative transport fuel market for compressed natural gas and its renewable form biomethane in a number of EU Member States. Primarily focussing on a combination of biomethane and compressed natural gas (bio-CNG), this paper analyses the key considerations to develop a strategic infrastructure framework for bio-CNG and defines the criteria for the placement of public access refuelling stations in order to satisfy legislative requirements, commercial considerations, strategic placement and natural gas network infrastructure utilisation. This paper devises a strategic infrastructure framework on which a national public access refuelling network for bio-CNG could be provided for Ireland as a template and for other Member States with similar infrastructure and renewable requirements to follow. The framework includes the provision of 22 bio-CNG refuelling installations in strategic locations across the country. Highlights: Proposes criteria to develop a bio-CNG infrastructure framework in Ireland. Devises a bio-CNG infrastructure framework to influence Irish transport policy. Proposes 22 bio-CNG refuelling station locations to initiate the Irish market. Nine stations are located in areas with high biomethane production potential. This framework complies with the EU Alternative Fuels Infrastructure Directive.